Friends and Allies: LGBT+ Inclusion in Statistics and Data Science. Issue 3 (29th May 2019) - Thornton, Suzanne; Green, Brittany; Benn, Emma
Abstract: At a conference last year, Suzanne Thornton, Brittany Green and Emma Benn organised a panel session to share advice and recommendations for making the statistics and data science community more inclusive and supportive of gender non-conforming and LGBTQ persons. Here they summarise their discussion in the hope of continuing the conversation